2019
DOI: 10.1093/infdis/jiy710
|View full text |Cite|
|
Sign up to set email alerts
|

Diverse Clinical Isolates of Mycobacterium tuberculosis Develop Macrophage-Induced Rifampin Tolerance

Abstract: Mycobacterium tuberculosis develops tolerance to multiple antibiotics when residing in host macrophages. We demonstrate that macrophage-induced tolerance to rifampin is common across major lineages of M. tuberculosis, except for Beijing-family lineage 2 strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Due to the fact that intracellular pathogens develop persistence phenotypes within the host and cellular environmental stresses play significant role in this process [ 61 , 62 , 63 ], we examined MAH susceptibility to antibiotic treatment in combination with SCFA within macrophages. The treatment with both antibiotics was found to be more lethal in combination with SCFA, significantly inhibiting intracellular MAH104 growth within the host macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that intracellular pathogens develop persistence phenotypes within the host and cellular environmental stresses play significant role in this process [ 61 , 62 , 63 ], we examined MAH susceptibility to antibiotic treatment in combination with SCFA within macrophages. The treatment with both antibiotics was found to be more lethal in combination with SCFA, significantly inhibiting intracellular MAH104 growth within the host macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…These conditionally-active compounds would be overlooked in other screens against extracellular bacteria. There is accumulating evidence that intracellular bacteria are both heterogenous and antibiotic tolerant ( Vijay et al, 2017 ; Adams et al, 2019 ; Mandal et al, 2019 ; Mishra et al, 2019 ; Nair et al, 2019 ), and this may be one reason why drug treatment to achieve sterilization takes >4 months. The inclusion of compounds which specifically target intracellular bacteria in a drug regiment could be one approach to shorten therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent THP-1 macrophage infection study by Adams et al . ( 2019 ) demonstrated that macrophages induced increased persistence (i.e. higher levels of heterotolerance) to isoniazid in MTBC strains belonging to L1, L2, L3 and L4.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Adams et al . ( 2019 ) showed that macrophages also induced increased persistence to rifampicin in L1, L3 and L4 strains, but not in L2 Beijing strains. This study therefore suggests that the magnitude of persistence or heterotolerance is dependent on the bacterial genotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation